FINANCING OF THE PROGRAMME TO COMBAT LAND DEGRADATION ON THE "PLATEAU ADJA" IN BENIN - DOSSA, Alfred (My University, 2020)
Land degradation, caused by water and wind action and reinforced by human activities, reduces agricultural yield and income and lowers economic growth, especially in poor countries such as Benin 1. The objective of this research is to estimate the funding for the programme to combat land degradation on the Adja Plateau. The Contingent Valuation Method (CVM) was used to obtain the total amount of households’willingness to pay (WTP) using the probit model. Then the tobit2 model wastested using the two-stage 3method to control the sample selection bias of 267 households. The estimation resultsgive an average WTP of 1557 FCFA / month / hectare. For a cropping season of 201,739 hectares in 2019, the total WTP is estimated at 3,769,291,476 FCFA/year. Land degradation, caused by water and wind action and reinforced by human activities, reduces agricultural yield and income and lowers economic growth, especially in poor countries such as Benin 1. The objective of this research is to estimate the funding for the programme to combat land degradation on the Adja Plateau. The Contingent Valuation Method (CVM) was used to obtain the total amount of households’willingness to pay (WTP) using the probit model. Then the tobit2 model wastested using the two-stage 3method to control the sample selection bias of 267 households. The estimation resultsgive an average WTP of 1557 FCFA / month / hectare. For a cropping season of 201,739 hectares in 2019, the total WTP is estimated at 3,769,291,476 FCFA/year.
Keywords: Financing; land degradation; selection model; "Plateau Adja"; Benin